Understanding the Central Visayas cluster of the Daughters of Charity schools as a learning organization - Amar, Ana J., DC (Animo Repository, 2018)
This case study was conducted to understand clustering as a style of leadership and management espoused by the Daughters of Charity Educational System Central Visayas Cluster. The research design was a single case study with embedded units. The cluster was taken as a single case with the three member schools as its embedded units. The data was collected through survey interview, individual and group interviews, and document analysis on the benefits of clustering for its member schools. These data were coded following Creswell (2014) Data Analysis in Qualitative Research getting the interrelated themes and the emerging themes. The participants of the study were the present and past members of the Servant – Leadership Team (SLT) of the Central Visayas Cluster, and the non-SLT members but are actively involved in the operation of the cluster. The number of participants is twenty seven (27) and purposive sampling was used. The framework used in this study is the Core Disciplines of the Learning Organization such as Personal Mastery, Building Shared Vision, Mental Models, Team Learning, and Systems Thinking based from Peter Senge’s The Fifth Discipline. The results of the study reveal that the Central Visayas Cluster as management strategy style empowers the leaders especially the Lay Mission Partners. It transforms their attitude towards generous sharing of resources both human and material. Clustering has its own Commission on Education Ministry of the Congregation, to review the cluster operational system for a better service to the poor.